Hybrid Narratives: Exploring Cultural Fusion in The Goats in the Cemetery by Kanogpong Songsompun - Amelia Gustiari; Sulastri Sulastri; Zurmailis Zurmailis (Muslim English Literature, 2023)
The short story "The Goats in the Cemetery" by Kanogpong Songsompun, a Buddhist writer from Southern Thailand, incorporated Islamic terminologies as its opening and closing lines, highlighting the presence of hybridity between Islam and Buddhism in the region. This research aimed to explore and analyze the depiction of hybridity between Islam and Buddhism in Southern Thailand, as observed in Songsompun's writing. The focus was on the coexistence and mutual respect between the majority Malay-Muslim villagers and the Thai-Buddhist capital holders in the face of a modernization program. This research employs Homi K. Bhabha's postcolonial theory. The analysis revealed that the short story effectively portrayed the villagers' anxiety caused by the modernization program. Despite the religious differences, with the villagers being predominantly Malay-Muslims and the capital holders being Thai-Buddhists, they lived harmoniously, demonstrating mutual respect and coexistence. Moreover, Songsompun's writing challenged the notion of Islam as a restricted religion by presenting it from a global perspective within the context of his work. The research findings emphasized the potential for hybridity to thrive when different religious communities respect and tolerate one another. This research contributes to a broader understanding of the manifestations of hybridity between Islam and Buddhism in societies that embrace multiple religions. It underscores the importance of mutual respect and coexistence, serving as a reminder of the possibilities for cultural hybridity and harmonious coexistence in diverse communities.